Modelling of size distribution of blocky retained austenite in Si-containing bainitic steels. Issue 1 (2nd January 2018) - Guo, L.; Roelofs, H.; Lembke, M. I.; Bhadeshia, H. K. D. H.
ABSTRACT: A model for estimating the blocky retained austenite size distribution in Si-containing steels has been developed for the first time, based on the geometric partitioning of prior austenite grains by bainite sheaves. A random volume allocation method for the two new compartments formed by the formation of one bainite sheaf is adopted for reasons detailed in the text. Random selection of the compartment for subdivision is also employed at each step. The model has been verified experimentally using Si-containing bainitic steels.